EKSPLORASI MAKNA ISLAM DALAM AL-QUR’AN PERSPEKTIF MUHAMMAD ASAD - Febriyanti, Eka; Islamiyah, Islamiyah (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2025)
This article examines the meaning of Islam as portrayed in the Qur’an from Muhammad Asad’s perspective. It explores the interpretation of sacred texts by emphasizing complete surrender to Allah. Asad argues that Islam is not merely a set of rituals or legal rules but a profound spiritual realization that requires total commitment of the heart, mind, and soul to the oneness of God. The study analyzes Qur’anic verses that affirm true salvation rests on sincere belief, confidence in the Day of Judgment, and the performance of virtuous deeds. Furthermore, the article discusses the principle of religious freedom that forbids coercion in matters of faith, allowing individuals to choose their spiritual path without force. Asad’s inclusive approach, which rejects sectarian exclusivity, paves the way for interfaith dialogue and highlights the universal values of Islam that promote human dignity and social justice. The study concludes that the essence of Islam, defined by complete surrender to Allah, is relevant for achieving global harmony and peace. This research offers fresh insights to support mutual understanding and cooperation among diverse religious communities and emphasizes Muhammad Asad’s vital role in renewing Qur’anic interpretation to foster contemporary religious comprehension and spiritual harmony around the world. Overall unity.